Learning to Be a Responsive, Authoritative Teacher: Effects of Experience and Age on Teachers' Interactional Styles. Issue 1 (2nd January 2021) - Torff, Bruce; Kimmons, Kathleen
Abstract: Investigating the development of teachers' interactional styles (related to "authoritative teaching"), survey research examined how interactional styles are predicted by teaching experience, age, and educational attainment, as well as gender. Secondary teachers (N = 272) completed an instructional-style scale measuring preferences concerning response, demand, and control. More experienced teachers, younger teachers, and females were significantly higher in response. No differences were found for demand or control, and educational attainment had no effect.